2020
DOI: 10.1002/brb3.1654
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electroconvulsive therapy in patients with “less treatment‐resistant” depression by the Maudsley Staging Model

Abstract: Introduction Electroconvulsive therapy (ECT) is an effective treatment for patients with mood disorders and is most often used for treatment‐resistant cases. This study aimed to examine the effectiveness of ECT in a real‐world treatment sample in a Chinese psychiatric hospital which included both treatment‐resistant and nontreatment‐resistant patients. Methods An observational study of symptom outcomes from admission to the time of discharge was conducted with 37 inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…However, a study that investigated the effectiveness of ECT reported that inpatients who were identified through the MSM 10.3389/fnins. 2022.1046920 to have TRD (n = 18) did not differ significantly from inpatients without TRD in terms of their depression scores at the time of psychiatric discharge (Ma et al, 2020). In addition, Hägg et al (2020) compared patients with TRD who were identified through various staging methods, and they reported that MSMidentified TRD [adjusted hazard ration (aHR) = 0.95, 0.94-0.97] and MGH-identified TRD (aHR = 0.92, 0.92-0.94) were associated with a slightly reduced risk, whereas ESM-identified TRD was associated with higher non-significant, marginal risk for psychiatric hospitalization (aHR = 1.03, 95% confidence interval = 1.00-1.05).…”
Section: Introductionmentioning
confidence: 80%
“…However, a study that investigated the effectiveness of ECT reported that inpatients who were identified through the MSM 10.3389/fnins. 2022.1046920 to have TRD (n = 18) did not differ significantly from inpatients without TRD in terms of their depression scores at the time of psychiatric discharge (Ma et al, 2020). In addition, Hägg et al (2020) compared patients with TRD who were identified through various staging methods, and they reported that MSMidentified TRD [adjusted hazard ration (aHR) = 0.95, 0.94-0.97] and MGH-identified TRD (aHR = 0.92, 0.92-0.94) were associated with a slightly reduced risk, whereas ESM-identified TRD was associated with higher non-significant, marginal risk for psychiatric hospitalization (aHR = 1.03, 95% confidence interval = 1.00-1.05).…”
Section: Introductionmentioning
confidence: 80%
“…Terapia elektrowstrząsowa (ECT) jest znana ludzkości od wielu dekad, a za jej pioniera w Polsce uważa się wileńskiego lekarza Klemensa Maleszewskiego który już w 1861 roku z sukcesem wykorzystał prąd elektryczny do leczenia pacjenta z katatonią [11]. Terapia elektrowstrząsowa jest powszechnie uważana za najskuteczniejszą metodę leczenia depresji i najczęściej jest stosowana gdy leki antydepresyjne nie przyniosą odpowiedniej poprawy klinicznej na przykład w depresji lekoopornej (TRD) oraz w nagłych przypadkach psychiatrycznych takich jak próba samobójcza, ciężka katatonia, złośliwy zespół neuroleptyczny [9] . Metoda skuteczna w leczeniu depresji jedno-i dwubiegunowej [8], odpowiednia dla pacjentów w podeszłym wieku i z chorobami towarzyszącymi w tym chorobami serca, płuc i neurologicznymi [10].…”
Section: Słowa Kluczoweunclassified
“…Terapia elektrowstrząsowa jest powszechnie uważana za najskuteczniejszą metodę leczenia depresji i najczęściej jest stosowana gdy leki antydepresyjne nie przyniosą odpowiedniej poprawy klinicznej na przykład w depresji lekoopornej (TRD) oraz w nagłych przypadkach psychiatrycznych takich jak próba samobójcza, ciężka katatonia, złośliwy zespół neuroleptyczny [9] . Metoda skuteczna w leczeniu depresji jedno-i dwubiegunowej [8], odpowiednia dla pacjentów w podeszłym wieku i z chorobami towarzyszącymi w tym chorobami serca, płuc i neurologicznymi [10]. Obecnie ECT jest uznawane za najskuteczniejszą metodę leczenia niektórych rodzajów depresji, a ponadto żadne badanie kontrolowane nie wykazało, że inna forma leczenia jest lepsza od ECT w krótkoterminowym leczeniu ciężkiej depresji.…”
Section: Słowa Kluczoweunclassified
“…However, others did not find a difference in ECT-effectiveness between patients with TRD versus non-treatment resistance, but the included sample size was small. 21 To our knowledge, the DM-TRD has not yet been investigated regarding its predictive value for treatment outcome in ECT.…”
Section: Introductionmentioning
confidence: 98%
“…The tendency to position ECT as "treatment-of-last-resort" may decrease the likelihood of beneficial outcome, but the impact of the level of treatment resistance on ECToutcome has only been studied in small samples. 20,21 In ECT patients, examined with the MSM, Van Diermen et al 20,22 have shown that a longer depression duration, less severe depression severity and having had more failed antidepressants were associated with decreased ECT-effectiveness. However, others did not find a difference in ECT-effectiveness between patients with TRD versus non-treatment resistance, but the included sample size was small.…”
Section: Introductionmentioning
confidence: 99%